The Effects of Ethnoscience Integrated Problem-Based Learning Models on Students' Critical Thinking Skills - Gummah, Syifaul; Fitri, Muliana; Prayogi, Saiful; Asy'ari, Muhammad (Universitas Pendidikan Mandalika, 2023)
In the contemporary educational landscape, cultivating critical thinking skills is imperative for students to thrive in the 21st century. Recognizing that critical thinking is not an instantaneous process, it is essential to employ didactic mechanisms specifically designed to hone this skill. Traditional expository teaching methods have been deemed insufficient in fostering critical thinking among students. Therefore, effective pedagogical intervention models are warranted, allowing students to engage authentically in everyday contexts. This study assesses the impact of an ethnoscience-integrated problem-based learning model on students' critical thinking skills. Employing a quasi-experimental design with a non-equivalent control group, the research unfolded in a secondary school in Mataram City, with a sample of 66 students divided into experimental and control classes. The experimental class experienced instruction through an ethnoscience-integrated problem-based learning model, while the control class adhered to traditional (expository) teaching methods. Critical thinking skills were assessed using a validated test instrument encompassing analysis, inference, evaluation, and decision-making indicators. Descriptive and statistical analyses were applied to scrutinize the data. The results revealed that students in the experimental class exhibited higher levels of critical thinking skills than their counterparts in the control class, which was statistically significant. In conclusion, this research establishes a significant positive influence of the ethnoscience-integrated problem-based learning model on students' critical thinking skills. Furthermore, it reaffirms the inadequacy of traditional (expository) teaching in enhancing students' critical thinking abilities.